Factors contributing to mental illness relapses in the mentally ill patients at Chainama Hills Hospital, Zambia - Makasa, Cephas (Lusaka: University of Zambia , School of Medicine, 2015)
Relapses in mentally ill patients are quite common worldwide and affect both developed and devloping countries. Relapses pose a serious concern in mentally ill patients as successive relapses reduce the degree and duration of remission, worsen disability and increase refractoriness to future treatments. Furthermore relapses lead to readmissions which result in challenges such as shortage of beds, overcrowding, strain on the few members of staff and other resources. the main objective of this study was to explore the factors contributing to relapses in mentally ill patients at Chainama Hills Hospital.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Mental health services; Mental Disorders--therapy.